Precompetition orthopedic Assessment of international elite football players - Junge, A.; Grimm, K.; Feddermann, N.; Dvorak, J. (Clinical Journal of Sport Medicine, 2009)
Objective: To assess the feasibility of the orthopedic part of a standardized precompetition medical assessment (PCMA) in teams from countries with variable medical background and to collect data on medical history and musculoskeletal findings of the players participating in the 2006 FIFA World Cup.